About the problems of teaching future teacher-trainers in the condition of informatization of education - B K Mukhamedzhanov (RUDN Journal of Informatization in Education, 2014)
In this article are considered actuality of informatization of professional education, about problems of readiness to use information and computer technology of professional activity of future teacher-trainers. Authors state that according to the accepted concept of the education, the offered technology of creation of models of activity of future teacher-trainers in most part has to be realized on the basis of information technology. Training of future teacher-trainers on the computer technologies, created on the basis of activity models of specialists, is applicable for model of training of specialists to natural-science specialties.